부 · 모의 양육행동과 유아의 외현화 문제행동의 관계에서 정서조절능력의 매개효과 - 최정은(Jung Eun Choi); 이소연(SoYean Lee) (Korean Journal of child studies, 2017)
Objective: The purpose of this study was to investigate the mediating effects of emotional regulation abilities on the relationship between parenting behavior and preschoolers' externalizing behavior problems. Methods: A survey was conducted with the parents of 166 preschoolers; the children were attending seven different daycare centers in Seoul. Results: The results were as follows: First, emotional regulation abilities fully mediated the relationship between fathers' rejection-restriction parenting behavior and externalizing behavior problems. Second, emotional regulation abilities fully mediated the relationship between mothers' warmth-acceptance, rejection-restriction, and permissive-neglectful parenting behavior and externalizing behavior problems. Third, after controlling for fathers' parenting behavior, emotional regulation abilities fully mediated the relationship between mothers' parenting behavior and externalizing behavior problems. Conclusion: Both parenting behavior and emotional regulation abilities should be considered when attempting to understand the development of preschoolers' externalizing behavior problems. In particular, the results from this study stress the important role of emotional regulation abilities in decreasing externalizing behavior problems and buffering against the influence of negative parenting behavior.